Studying Digital Library Users Over Time: A Follow-up Survey of Early Canadiana Online - Joan Cherry; Wendy Duff (Information Research: An International Electronic Journal)
This paper reports the findings of a second user survey of a digital library collection of Early Canadiana materials. The main purpose of the study was to investigate whether the user group or the nature of use had changed since the first survey conducted a year earlier. As in the first survey we also wanted to gather feedback on satisfaction levels and suggestions for improvements to the Early Canadiana Online (ECO) site. A new section was added to the second survey to explore the use of ECO in teaching and research. Overall, findings showed that the user group and nature of use of the materials were remarkably similar to the first survey. Enthusiasm for ECO remained high but many of the requests for changes to existing features and the suggestions for enhancements to the site were the same as those in the first survey. The survey revealed that respondents who used ECO for teaching and research differed from other respondents in a number of ways. We close by discussing the implications of these findings for digital libraries in general and the value of studying digital library users over time.